Isolated traumatic dislocation of the posterior tibialis tendon: a case report - Damazio Heluy, Gustavo; Filipi Bernini, Alesson; Rodrigues Fernandes Júnior, Lincoln; Alves Silveira Monteiro, Luciana; Lazaroni, Pedro Sebastião de Oliveira (Journal of the Foot & Ankle, 2025)
This case report describes a 65-year-old female patient with no previous comorbidities who suffered a traumatic dislocation of the posterior tibialis tendon during domestic activities. The initial diagnostic suspicion was a sprain; however, after suggestive physical examination and subsequent magnetic resonance imaging, dislocation of the posterior tibialis tendon was confirmed. The patient was submitted to tendon reduction, repair, and retinaculum reinforcement using tibial periosteal flaps. No complications occurred postoperatively, and after six months, the patient returned to her usual activities. Level of Evidence IV, Therapeutic Study; Case Report.